Analysis of Carding Crime as A Form of Cyber Crime in Indonesian Criminal Law - Manaf, Idham (YHMM PUBLISHING, 2023)
Technological developments have had a positive impact on human life but on the one hand they have also had a negative impact which has led to the emergence of a new type of crime in the field of technology called cybercrime, namely the crime of credit card data theft. Carding is credit card fraud where the perpetrator knows someone's credit card number that is still valid to use, then the perpetrator can buy goods online whose bill can be addressed to the original owner of the credit card, while the perpetrator is called a carder. This type of research uses a normative approach. The data collection technique is through the literature and laws and regulations then analyzed descriptively qualitatively. Carding crimes in Indonesia are charged with legal regulations using Articles 362, 363, and 378 of the Criminal Code and Article 31 paragraphs 1 and 2 of the 2008 ITE Law. With the existence of legal regulations regarding carding crimes, it is expected to reduce the number of carding crimes in Indonesia. Prevention of carding crimes by using penal or repressive means is by imposing criminal sanctions and trying to take action by correcting the perpetrators and non-penalty/preventive means, which include preaching activities, legal counseling lectures, counseling in the fields of religion, ethics and law